An application of knowledge management in industry sector: a case study of five Thailand industries - Sinthavalai, Runchana; Meemongkol, Napisphon; Phenglong, Nawaporn (Asia-Pacific Journal of Science and Technology, 2017)
This study attempted to ascertain the implementation of knowledge management in an industrial sector. In other words, the study focused on a big picture of knowledge management implementation in the industries. Five industrial sectors; automotive, office machinery, seafood processing, electronic equipment, chemicals and chemical products, were focused. There were 966 organizations surveyed by mailed questionnaires. The survey revealed that 81.1 percent of responses have not applied knowledge management in their organizations. The main reason was lack of knowledge in the concept of knowledge management. 19.9 percent of responses claimed themselves working on knowledge management formally. The ultimate goals for implementing knowledge management were highlighted as competency development and job improvement. Besides, the actual benefits were highlighted as improving the efficiency and productivity. The main obstacles were concluded as lack of process for knowledge sharing, inappropriate technology, and uncoordinated staff. In fact, those were theoretically considered as main driver for knowledge management. For tools and techniques, a small group activity and a document system were popularly applied. In addition, tools and techniques enabling a knowledge transfer are typically used comparing to tools for the knowledge access. This research also focused on the factor analysis. Three issues were statistically tested for their factors; benefits of knowledge management, obstacles in implementing, and knowledge management tools. The factors, which were considered, were type of industry, organization size, and experience in knowledge management.